The EvCA project: A brief history. Issue 5 (23rd April 2013) - Hordijk, Wim
<x xml:space="preserve">Abstract</x> This article presents a brief history of the Evolving Cellular Automata (EvCA) project. In the EvCA project, a genetic algorithm was used to evolve cellular automata to perform certain (nontrivial) computational tasks, in an effort to gain more insight into the question: "How does evolution produce sophisticated emergent computation in systems composed of simple components limited to local interactions?" Next to providing many interesting results and useful insights, the EvCA project seems to have spawned a whole research area of its own. Here, a brief overview is given of how it all started, developed, and inspired further work. © 2013 Wiley Periodicals, Inc. Complexity 18: 15–19, 2013